Immunodetection of EGF-receptor, C-erbB oncogenes and HSV-1 antigene in oral mucosal swab preparation from Kretek (Clove cigarette) smokers - Silvi Kintawati (Faculty of Dentistry Universitas Padjadjaran, 2008)
Smoking is the biggest factor for oral cavity malignancy. An oral cavity mucous swab was performed to 30 smokers (mild, moderate and severe) and 10 non-smokers which were followed by immunocytochemistry smear using the antibody for EGF-R, c-erbB, and HSV-1 antigens to reveal the effect of smoking on the occurrence of oral cavity malignancy. The results from this experiment are analyzed statistically using one-way Anava. It is discovered that based on the assessment of the expression level towards EGF-R, and C-erbB oncogene there is a very significant difference between the smoker group and non-smoker group (p < 0.01). Meanwhile, the results from the assessment towards HSV-1 oncogene do not show significant differences between the smoker group (mild, moderate and severe) and the non-smoker group (p > 0.05). The results of this study show that the more a person smokes, the higher possibility of oral cavity malignancy and that the antibody for EGF-R and c-erbB can be used as a marker for early detection of oral cavity malignancy caused by smoking.